Improvement in lung function and functional capacity in morbidly obese women subjected to bariatric surgery (Clinics, 2018)
OBJECTIVE: To determine whether weight loss in women with morbid obesity subjected to bariatric surgery alters lung function, respiratory muscle strength, functional capacity and the level of habitual physical activity and to investigate the relationship between these variables and changes in both body composition and anthropometrics. METHODS: Twenty-four women with morbid obesity were evaluated with regard to lung function, respiratory muscle strength, functional capacity, body composition, anthropometrics and the level of habitual physical activity two weeks prior to and six months after bariatric surgery. RESULTS: Regarding lung function, mean increases of 160 mL in slow vital capacity, 550 mL in expiratory reserve volume, 290 mL in forced vital capacity and 250 mL in forced expiratory volume in the first second as well as a mean reduction of 490 mL in inspiratory capacity were found. Respiratory muscle strength increased by a mean of 10 cmH2O of maximum inspiratory pressure, and a 72-meter longer distance on the Incremental Shuttle Walk Test demonstrated that functional capacity also improved. Significant changes also occurred in anthropometric variables and body composition but not in the level of physical activity detected using the Baecke questionnaire, indicating that the participants remained sedentary. Moreover, correlations were found between the percentages of lean and fat mass and both inspiratory and expiratory reserve volumes. CONCLUSION: The present data suggest that changes in body composition and anthropometric variables exerted a direct influence on functional capacity and lung function in the women analyzed but exerted no influence on sedentarism, even after accentuated weight loss following bariatric surgery.